Robots and the origin of their labour-saving impact - Fabio Montobbio; Jacopo Staccioli; Maria Enrica Virgillito; Marco Vivarelli (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2020)
This paper investigates the presence of explicit labour-saving heuristics within robotic patents. It analyses innovative actors engaged in robotic technology and their economic environment (identity, location, industry), and identifies the technological fields particularly exposed to labour-saving innovations. It exploits advanced natural language processing and probabilistic topic modelling techniques on the universe of patent applications at the USPTO between 2009 and 2018, matched with ORBIS (Bureau van Dijk) firm-level dataset. The results show that labour-saving patent holders comprise not only robots producers, but also adopters. Consequently, labour-saving robotic patents appear along the entire supply chain. The paper shows that labour-saving innovations challenge manual activities (e.g. in the logistics sector), activities entailing social intelligence (e.g. in the healthcare sector) and cognitive skills (e.g. learning and predicting).
Keywords: O33; J24; C38; 330; Robotic Patents; Labour-Saving Technology; Search Heuristics; Probabilistic Topic Models